Capitalism in the web of life : ecology and the accumulation of capital - Moore, Jason W. (Verso, 2015)
"Both green and red analyses of capitalism's deepening contradictions have acknowledged the close relation of economic and environmental crises. But environmentalists have not yet fully integrated social and historical factors in their scathing indictment of the current disaster. Capitalism in the Web of Life will undoubtedly help to change that. Charting the recurrent crises, and long cyclical expansions of capitalism as socio-ecological process over the past six centuries, Jason Moore provides a groundbreaking theory and historical account of capitalism's development that comprehends the transformation of nature as constitutive of capital accumulation. Along the way, he moves beyond the society/nature distinction that limits so much environmentalism"--